Multiplicity in entrepreneurship economic development of Malaysian smallholder farmers - Mustaffa, Muhammad Firos; Singaravelloo, Kuppusamy; Othman, Azmah (Allied Business Academies, 2019)
Land can be considered as economics generated space by farming communities, mostly located in rural areas. Modern agriculture has largely been accompanied with the development of new techniques in producing agriculture products. Current world agriculture demands for more agronomics at a higher level of economic development. Most agricultural activities are labour intensive and may or may not employ new technologies. Agriculture that lacks innovation has high tendencies to fail in modern farming practices leading to clogged economic growth in this sector. Use of modern technologies and machineries can overcome poverty problems among smallholder farmers by increasing farm production and supply into the market. Understanding the production of agriculture requires the knowledge of the distribution market till the ground level of the farm land. Nevertheless, poverty among smallholder farmers is always linked to lost opportunities of resources. This occurs due to the practice of conventional agricultural methods in farming, distance from market, and employment of outdated production equipment. Therefore, there is a high need for innovation, support of network and latest information on new equipment and technologies in the market be disseminated to increase farm production. To counter this, entrepreneurship mechanisms have been introduced by many developed countries in addressing poverty in this community. In current times, agropreneurship alone in farming is deficient in various angles, but multiple entrepreneurship has begun to emerge to support the smallholder farmers' talent, skills and ability to shape their economic growth and release them from the poverty trap. This paper intends to evaluate whether the multiple entrepreneurship implemented by Malaysian smallholder farmers is effective in raising income and their quality of well-being and poverty eradication in rural area. The discussion emphasizes on the serious need for modernization in agriculture through such entrepreneurship that are guided by government policies. © 2019 Academy of Entrepreneurship Journal.